Judith Butler on Gender Performativity - Kakoliris, Gerasimos (Dia-noesis: A Journal of Philosophy, 2025)
This article examines Judith Butler’s theory of gender performativity, a pivotal concept in contemporary feminist and queer theory. Originating from Butler’s Gender Trouble (1990) and further developed in Bodies That Matter (1993), the theory challenges traditional distinctions between sex and gender by arguing that both are socially constructed through performative acts. Butler critiques the binary notion that biological sex predetermines gender identity, instead proposing that gender is continually constituted through repeated social performances within a regulatory framework Butler calls the “heterosexual matrix”. Drawing on J.L. Austin’s speech act theory and Jacques Derrida’s concepts of citationality and iterability, Butler asserts that gender is not an inherent trait but an effect produced through iterative acts. The article also explores Butler’s engagement with Louis Althusser’s concept of interpellation to explain how individuals are assigned gender identities at birth. It highlights how normative gender constructs are maintained through social rituals and coercive mechanisms, but also how these norms can be destabilized through subversive repetitions, such as parody and drag. The discussion underscores Butler’s view of agency as emerging within the discursive constraints of gender norms, offering a pathway to challenge and transform these structures through performative resignification.